A Sociolinguistic Consideration of Intermediation in Greeting Discourse among the YoÌ€ruÌba of South West Nigeria - Opoola, Bolanle Tajudeen; Adeoye, Jelili Adewale (Universitas Sanata Dharma, 2019)
Existing studies on YoruÌ€baÌ greeting forms dwell on the appropriateness of their use, with respect to time of the year, event, condition, occupation, vocation, context, politeness and content. The studies portray greetings as discourse between two people or parties who are capable of exchangingÂ Â pleasantries. None of the existing works has discussed intermediation in greeting discourse among the YoruÌ€baÌ people such that greetings that are directed to the second person(s) such as toddlers, extremely sick persons, kings and the bereaved are answered on their behalf by a third party. This paper examines intermediation and the rationale in greeting discourse among the YoruÌ€baÌ people. The data for this study were drawn from participant observation, YoruÌ€baÌ literature texts, and YoruÌ€baÌ home movies. The Mutual Contextual Beliefs Theory of Pragmatics as proposed by Bach and Harnish (1979) was adopted for the data analysis. The study established, among other things, that greetings are sacrosanct in YoruÌ€baÌ culture and the answer/reply is obligatory, irrespective of the state, status, circumstance and condition of the person(s) being greeted. It is also shown that intermediation in greeting discourse could be for politeness, incapacitation, authority and educating the young ones.